Improving accuracy of elephant localization using sound probes. (1st January 2018) - Dissanayake, Chinthaka M.; Kotagiri, Ramamohanarao; Halgamuge, Malka N.; Moran, Bill
Abstract: Localization of elephants in the vicinity of villages is an important issue in mitigating human-elephant conflict. This paper proposes an inexpensive, effective and non-invasive framework that employs a sound probe technique with an acoustic sensor network to localize elephants. Incorporation of probes in our sensor network eliminates the requirement to explicitly measure temperature and wind velocity for accurate determination of sound velocity. A sensor network has been built and experiments performed by replaying recorded elephant sounds under three different environmental conditions. The results overall show that the system is capable of providing remarkable accuracy under distinct wind and temperature conditions. An identical experimental set up was used to localize wild elephants in Sri Lanka. Our approach enabled localization of wild elephants at a distance of over 500 m from the sensors to within 30 m, providing adequate time for the villages to take appropriate safety measures.